(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe anxiety among third-year students at Ha Dong Medical College in 2026. Methods: A cross-sectional descriptive study was conducted from October 2025 to June 2026 among 554 full-time third-year students. A census approach was applied, and all eligible students during the study period were invited to participate. Anxiety was assessed using the HAM-A. Data were collected using a structured questionnaire, entered, cleaned, and analyzed with SPSS 20.0 software. Results: Female students accounted for 82.9%, 57.4% were from rural areas, and 39.5% were living with their parents. Most participants did not use psychoactive substances, accounting for 89.9%; however, 36.8% reported psychological trauma and only 15.2% exercised regularly. The average percentages across HAM-A score levels were 49.06% for score 0; 36.13% for score 1; 12.24% for score 2; 2.12% for score 3, and 0.44% for score 4. Thus, students with no anxiety manifestations or only mild manifestations accounted for 85.19%, whereas severe and very severe manifestations accounted for only 2.56%. The more prominent domains were tension, cognitive symptoms, anxious mood, and insomnia. Conclusion: Anxiety among third-year students was mainly absent or mild; however, psychological symptoms and sleep disturbances were still relatively common. The school should strengthen early screening, school-based counseling, and supportive interventions to improve sleep and stress-coping skills for students.